Does resectoscope size play a role in formation of urethral stricture following transurethral prostate resection? - Mustafa Günes (International Brazilian Journal of Urology, 2015)
ABSTRACTBackground and aims:To investigate the possible effect of resectoscope size on urethral stricture rate after monopolar TURP.Materials and Methods:A retrospective study of 71 men undergoing TURP was conducted at two centers’ from November 2009 to May 2013. The patients were divided into one of two groups according to the resectoscope diameter used for TURP. Resectoscope diameter was 24 F in group 1 (n=35) or 26 F in group 2 (n=36). Urethral catheter type, catheter removal time and energy type were kept constant for all patients. Urethral stricture formation in different localizations after TURP was compared between groups.Results:There was no significant difference between the two groups in terms of age, pre-operative prostate gland volume (PV), prostate-specific antigen (PSA), maximal urinary flow rates (Qmax), International Prostate Symptom Score (IPSS) and post-voiding residual urine volume (PVR). The resection time and weight of resected prostate tissue were similar for both groups (p>0.05). A statistically significant higher incidence of bulbar stricture was detected in group 2 compared to group1 (p=0.018).Conclusions:The use of small-diameter resectoscope shafts may cause a reduction in the incidence of uretral strictures in relation to urethral friction and mucosal damage.